Clonal micropropagation of decorative cereal Molinia caerulea (L.) Moench - T. G. Lekontseva; A. V. Fedorov (Аграрная наука Евро-Северо-Востока, 2020)
The research is devoted to the development of clonal micro-propagation technology of the decorative cereal Molinia caerulea (L.) Moench. The concentration of 2.0 mg /l of cytokinin 6-benzylaminopurine (6-BAP) contributed to obtaining the maximum number of microshoots: 6.3 and 7.9 pcs. on Anderson's and Murashige-Skoog's (MS) media, respectively, which exceeded the control (by 4.7 and 6.3, respectively, with LSD05 = 2.3). The length shoots were observed on hormone-free media, this indicator significantly decreased with an increase in 6-BAP content. On Anderson and MS media with 1.0 mg/l 6-BAP, the shoot length averaged 21.5 and 26.4 mm, respectively, which made it possible to transplant them for rooting, bypassing planting on a medium for elongation. The inclusion of the Siliplant micro-fertilizer in the MS medium at doses of 1.0 and 2.0 ml/l contributed to a significant increase in shoot size, by 16.7 and 10.7 mm (LSD05 = 8.9), respectively, in comparison with the control (MS). It is recommended to use Anderson's medium and 0.5 mg/l of indole-3-acetic acid as a medium for rhizogenesis: after two weeks of cultivation, the regenerants had a standard appearance with developed roots suitable for planting for adaptation. At the adaptation stage, watering the substrate with the biofungicide «Trichoderma veride» according to the instructions and a cereals single spraying with the micro-fertilizer «Siliplant» at a dose of 1.5 ml/l contributed to their 100 % survival rate.